ANALISIS PENDAPATAN DAN KELAYAKAN USAHA INDUSTRI MEUBEL KAYU JATI (STUDI KASUS CV. KERAJINAN JEPARA KELURAHAN KELAPA LIMA KECAMATAN KELAPA LIMA KOTA KUPANG) - Diana Soli Laxina Ngongo; Paulus Un; Nixon Rammang (Wana Lestari, 2021)
The Purpose of this Research to know the amount of income, and to recognise the feasibility of the teak furniture industry. Data collection by interview using a questionnaire. Tabulated and analyzed using the formula calculation of Income and calculation of Break even Point. The results showed that in 2013 the income earned by CV. Jepara handicrafts amounted to Rp. 129,697,500, in 2014 Rp. 132,147,500, in 2015 the income obtained was Rp. 120,347,500, in 2016 the income obtained was Rp. 146,947,500, and in 2017 the income earned was Rp. . 136,847,500. In total the total income of CV. Jepara handicrafts from 2013 to 2017 amounting to IDR 665,987,500; with the average income of CV. Jepara handicrafts per year are Rp. 133,197,500 ,. This shows that the teak wood furniture industry CV. Jepara handicrafts are financially feasible to continue because they provide benefits for the owner. Meanwhile, the results of the BEP analysis show that the teak furniture industry business CV. Jepara handicrafts get BEP prices of IDR 2,920,340 / unit so producers have to set prices above IDR 2,920,340 / unit to make a profit. This is in line with what was done by CV. Jepara handicrafts by setting a price of Rp. 3,500,000 / unit so that the business gets a profit of Rp. 576,000 / unit. For BEP, the total production unit carried out by CV Kerajinan Jepara is 125 units / year so as not to experience profit or loss. While the average total production per year is 150 units / year so that CV. Jepara handicrafts experience a production gain of 25 units / year. It can be explained from the results of the BEP analysis that this business is feasible to develop and has received such good profits and with the assumptions used it turns out that this business still provides benefits for the Company.